Artificial Intelligence in Project Management - Zherder, Marina (2021)
Artificial Intelligence has gained a big interest from companies in all fields. Project management is marked as one of the potential areas for Artificial Intelligence application and can be influenced significantly by using the intelligent programs to ease the project managers life. In the research, current project managers’ work issues and considered improvements are identified to clarify the tasks that can be solved by various Artificial Intelligence methods. The potential use cases of AI implementation in the PM field were identified and evaluated by project managers and AI experts. Several tools aiming to help project managers by using Artificial Intelligence were found and analysed.